Effect of a humic bio-stimulant extracted from the banana rachis on the growth of banana seedlings (Musa AAA "Cavendish" subgroup 'Gran enano' clone). - Russo, Ricardo; Lugo, José; Arreola, Oscar; Rango, Omar A. (Agronomía Mesoamericana, 2016)
The main objective of this assay was to evaluate the effect of a humic extract, obtained from previously composted banana rachises, on the growth of banana seedlings under nursery conditions and compare it with a commercial humic acid. The results show that the humic extract at 1% significantly promoted the growth ofroots, foliar area, and biomass of leaves and pseudo-stalk of banana seedlings under nursery conditions.